A little triggy

Geometry Level 3

Let f ( n ) = sin n ( x ) + cos n ( x ) f(n)=\sin^n(x)+\cos^n(x) , where n n is a positive integer. Find f ( 3 ) f ( 5 ) f ( 5 ) f ( 7 ) \dfrac {f(3)-f(5)}{f(5)-f(7)} .

f ( 3 ) f ( 4 ) \frac {f(3)}{f(4)} f ( 1 ) f ( 3 ) \frac {f(1)}{f(3)} f ( 1 ) f ( 2 ) \frac {f(1)}{f(2)} f ( 1 ) f ( 7 ) \frac {f(1)}{f(7)}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 22, 2018

Let a = sin θ a=\sin \theta and b = cos θ b = \cos \theta . Then f ( n ) = a n + b n f(n) = a^n + b^n and f ( 2 ) = a 2 + b 2 = sin 2 θ + cos 2 θ = 1 f(2) = a^2+b^2 = \sin^2 \theta + \cos^2 \theta = 1 . Now consider

( a n + b n ) ( a 2 + b 2 ) = a n + 2 + b n + 2 + a 2 b 2 ( a n 2 + b n 2 ) f ( n ) f ( 2 ) = f ( n + 2 ) + a 2 b 2 f ( n 2 ) Note that f ( 2 ) = 1 f ( n ) f ( n + 2 ) = a 2 b 2 f ( n 2 ) f ( 3 ) f ( 5 ) f ( 5 ) f ( 7 ) = a 2 b 2 f ( 1 ) a 2 b 2 f ( 3 ) = f ( 1 ) f ( 3 ) \begin{aligned} (a^n+b^n)(a^2+b^2) & = a^{n+2}+b^{n+2} + a^2b^2(a^{n-2}+b^{n-2}) \\ f(n)\color{#3D99F6}f(2) & = f(n+2)+a^2b^2f(n-2) & \small \color{#3D99F6} \text{Note that }f(2) = 1 \\ \implies f(n)-f(n+2) & = a^2b^2f(n-2) \\ \implies \frac {f(3)-f(5)}{f(5)-f(7)} & = \frac {a^2b^2f(1)}{a^2b^2f(3)} = \boxed {\dfrac {f(1)}{f(3)}} \end{aligned}

Tharun Aju
Oct 21, 2018

Refer picture given above Please upvote lol

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...